Sharia Financial Literacy: Conceptualizing Its Role as a Moderator in the Relationship Between Personality Traits and Investor Risk Behavior - Dian Essa Nugrahini; Verina Purnamasari; Diah Ayu Kusumawati (Universitas Darussalam Gontor, 2024)
Investment decisions are influenced by inherent psychological and emotional factors, undergoing a filtration process shaped by various emotional and psychological elements. The Big Five personality traits play a significant role in shaping attitudes and behaviors, exerting a causal impact on investor decision-making. Despite possessing knowledge and professional training, investors may occasionally make suboptimal financial decisions due to the influence of emotions, cognitive errors, and psychological biases. This study seeks to explore the correlation between personality traits and the inclination towards risk in investors' decision-making regarding investments. Additionally, the research investigates the impact of Sharia financial literacy on the connection between personality traits and investor risk behavior. Utilizing a quantitative methodology, the study employs a survey as the data collection method, with the findings analyzed through the partial least squares structural equation modeling (PLS-SEM) technique.